2010
DOI: 10.1055/s-0030-1250606
|View full text |Cite
|
Sign up to set email alerts
|

Goldenseal (Hydrastis canadensisL.) Extracts Synergistically Enhance the Antibacterial Activity of Berberine via Efflux Pump Inhibition

Abstract: Goldenseal (Hydrastis canadensis L.) is used to combat inflammation and infection. Its antibacterial activity in vitro has been attributed to its alkaloids, the most abundant of which is berberine. The goal of these studies was to compare the composition, antibacterial activity, and efflux pump inhibitory activity of ethanolic extracts prepared from roots and aerial portions of H. canadensis. Ethanolic extracts were prepared separately from roots and aerial portions of six H. canadensis plants. Extracts were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 23 publications
3
103
0
1
Order By: Relevance
“…The present study did not assess all efflux pump systems, so that the possible participation of efflux pumps other than MexXY-OprM cannot be ruled out. Several studies indicated that the weak antibacterial effect of BBR was mainly due to the low accumulation of intracellular BBR, and drugs that increased the intracellular BBR concentration were able to promote the antibacterial effect of BBR (25)(26)(27)(28). The present study observed that IMP significantly increased the intracellular BBR fluorescence.…”
Section: Discussionsupporting
confidence: 59%
“…The present study did not assess all efflux pump systems, so that the possible participation of efflux pumps other than MexXY-OprM cannot be ruled out. Several studies indicated that the weak antibacterial effect of BBR was mainly due to the low accumulation of intracellular BBR, and drugs that increased the intracellular BBR concentration were able to promote the antibacterial effect of BBR (25)(26)(27)(28). The present study observed that IMP significantly increased the intracellular BBR fluorescence.…”
Section: Discussionsupporting
confidence: 59%
“…BBR has been reported as an isoquinoline alkaloid with poor bioavailability (43). Some studies have demonstrated that the weak antibacterial effect of BBR was mainly due to the low concentration of intracellular BBR, and agents which could promote the ingression of BBR were able to enhance the antibacterial effect of BBR (29,(44)(45)(46). In this study, we postulated that FLC could promote the ingression of BBR.…”
Section: Discussionmentioning
confidence: 83%
“…There is some justification in the scientific literature for the effectiveness of Hydrastis canadensis L. (Ranunculaceae) and its constituents as antidiarrheal and antimicrobial agents (Cybulska et al, 2011;Ettefagh et al, 2011;Junio et al, 2011). Traditionally, H. canadensis was used by the Iroquois for gastrointestinal issues .…”
Section: Hydrastis Canadensismentioning
confidence: 99%